A Method of Quantifying Microangiograms - Wilson, J. W.; Arighi, Mimi (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
A method is proposed which can quantify the vascularity depicted in microangiograms. Total vascular area depicted in the microangiogram is measured using an image analyser. Vessel diameters and frequency are determined using standard stereological methods. Using the incidence of measured vessel diameters, the measured vascular area, and minimal mathematical manipulation, a distribution curve of possible vascular volumes can be constructed. When combined with sample volume, statistical data relevant to vessel diameters and volumes can be derived. This calculation is not meant as a substitute to stereological methods for quantifying vascularity using thin sections, only as a quantitative adjunct to microangiograms and descriptive microangiography.A method is proposed which can provide statistical data relevant to vessel diameters and volumes depicted in microangiograms.
Keywords: Microangiogram; vascular volume; vessel diameter; statistical quantification